Analisis Pemicu Internal Dan Eksternal Pada Implikasi Perencanaan Produksi Dalam Sistem Supply Chain Management - Purba, Nabillah; Sitorus, Nurbaina Junita; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
In the manufacturing industry, the main activity is to convert various raw materials and their supporting materials into semi-finished goods or finished goods, which are then distributed to customers. By carrying out various stages in the process, what is called a Supply Chain or supply chain basically already formed and implemented. This study aims to determine the triggering factors in the strategy of building a plan that focuses on the concept of supply chain management. Starting from demand forecasting, to the stage of supplying raw materials. This study uses a descriptive qualitative research method because the research method used to examine the condition of the object and variable as the key instrument. Using literature studies as a reference function as well as various reference sources from figures and experts. The data that has been collected is analyzed using steps that are often called triangulation, proposed by (Sugiyono, 2010:243), namely: (1) data reduction, (2) data display, (3) conclusion. Some of the production planning functions are: a) Ensuring sales plans and production plans are consistent with the company's strategic plan b) As a performance measurement tool for the production planning process c) Ensuring production capability is consistent with the production plan d) Monitoring the finished product results to achieve production targets and strategic plans e) Directing the preparation and implementation of the master production schedule The objectives of production planning are: a) Forecast product demand expressed in the number of products as a function of time b) Determine the amount when ordering raw materials and components in an economical and integrated manner c) Establish a balance between the level production requirements, order fulfillment techniques, as well as monitoring finished product inventory levels at any time.